Granular Flow: From Dilute to Jammed States - Shi, Hao; Vescovi, Dalila; Singh, Abhinendra; Roy, Sudeshna; Magnanimo, Vanessa; Luding, Stefan (Granular Materials, 2017)
Particulate systems and granular matter display dynamic or static, fluid‐ or solid‐like states, respectively, or both at the same time. The mystery of bridging the gap between the particulate, microscopic state and the macroscopic, continuum description is one of the challenges of modern research. This book chapter gives an overview of recent progress and some new insights about the collective mechanical behavior of granular, deformable particles.<br
Keywords: rheology; solid‐fluid granular behavior; micro‐macro transition; numerical simulations